The Effect of Financial Ratios on Financial Distress in Retail Sub-Sector Companies Listed on the Indonesia Stock Exchange - Yulfanis Aulia Masrifa, Andyni; Ayu Lestari, Mira (Research Horizon, 2025)
Financial distress refers to a condition in which a company experiences financial difficulties that hinder its ability to meet obligations. This issue is particularly relevant for retail companies, as they face intense competition, changing consumer behavior, and external economic pressures. Understanding the determinants of financial distress is important to provide early warnings for managers and stakeholders in maintaining company sustainability. This research aims to investigate the impact of financial ratios on financial distress among retail companies listed on the Indonesia Stock Exchange from 2019 to 2022. The financial ratios tested include the current ratio, debt to asset ratio, return on assets, total asset turnover, and sales growth. The study employs quantitative data and a purposive sampling method, selecting 15 retail companies, which yields a total of 60 samples. Logistic regression analysis was conducted using SPSS version 27 to test the relationships between independent variables and financial distress, as measured by the Altman Z-score. The findings reveal that none of the financial ratios, current ratio, debt to asset ratio, return on assets, total asset turnover, and sales growth, have a significant effect on financial distress. This suggests that other factors beyond traditional financial ratios may better explain financial distress.